Evaluating Vancomycin Monotherapy and Dual Therapy with Nifuroxazide for Medium–Severe Clostridioides Difficile Infection - Jasna Rahimić; Ervin Alibegović; Lana Lekić; Marijana Marković Boras; Amina Džidić-Krivić; Esma Karahmet Farhat; Emina Karahmet Sher (Antibiotics)
Background: All currently used therapeutic protocols and drugs for Clostridioides difficile infection (CDI) treatment do not have a satisfying success and usually cost a lot. Objectives: To compare the efficacy of vancomycin monotherapy vs modified dual therapy with vancomycin + nifuroxazide as a therapeutic protocol for a medium–severe form of CDI. In addition, the effects of a modified therapeutic protocol with standard monotherapy on the number of stools and stool consistency in a medium–severe CDI will be compared. Materials and Methods: A prospective, randomized, controlled clinical trial that included 60 patients divided into two groups was conducted. One group of patients was treated with vancomycin monotherapy. The other group was treated with the modified therapeutic protocol (vancomycin + nifuroxazide). Results: The modified therapy with vancomycin + nifuroxazide demonstrated enhanced pharmacological efficacy in the management of CDI compared to the standard vancomycin monotherapy. Patients treated with dual therapy reported a significantly lower number of stools in first, second and third control; first control (4.47 ± 2.20 compared to 5.70 ± 1.91 in vancomycin group (p = 0.024)), second control (2.37 ± 0.85 compared to 3.13 ± 0.90 in vancomycin group (p = 0.001)), and third control (1.53 ± 0.51 compared to 1.80 ± 0.61 in vancomycin group (p = 0.035)). Also, the first and third controls noted significant improvements in stool consistency, measured as a decrease in the number of completely watery stools (p = 0.011 and p < 0.001, respectively). Conclusions: Nifuroxazide and vancomycin have demonstrated accelerated improvement in patient status and hold promise as a novel dual therapeutic regimen for managing patients diagnosed with a medium–severe form of CDI.